Implementation of Inquiry Learning through Experiments in Developing Students' Procedural Skills Aspects - Hamidiah, Hamidiah; Fitriani, Henni; Dewi, Ucia Mahya; Fatmi, Nuraini; Hasanah, Adinda; Salsabila, Soraya Berlianda (SAINTIS Publishing, 2024)
The rapid advancement of science and technology demands education to equip students with critical thinking, creativity, and problem-solving skills. Science education, particularly chemistry, plays a vital role in fostering these skills through appropriate teaching approaches. However, chemistry learning at SMA Negeri 1 Syamtalira Bayu, North Aceh, still faces challenges such as low student interest, dominance of lecture-based methods, and weak psychomotor skills. This study aims to analyze the effectiveness of the inquiry-based experimental learning model in enhancing students' procedural skills. The research employed a mixed-method approach with an exploratory sequential design, involving two classes: experimental and control. The results showed that students in the experimental class experienced significant improvements in procedural skills, such as preparation, execution of experiments, observation, and collaboration. The inquiry approach encouraged active student engagement and the development of scientific attitudes. Compared to conventional methods, this model proved to be more effective in developing students’ psychomotor skills. Therefore, implementing inquiry-based experimental learning is recommended as an innovative strategy in chemistry education to foster active, skilled, and scientifically minded students.